Analysis of cross-reactivity among flaviviruses using sera of patients with dengue showed the importance of neutralization tests with paired serum samples for the correct interpretations of serological test results for dengue. Issue 5 (May 2023) - Maeki, Takahiro; Tajima, Shigeru; Ando, Naokatsu; Wakimoto, Yuji; Hayakawa, Kayoko; Kutsuna, Satoshi; Kato, Fumihiro; Taniguchi, Satoshi; Nakayama, Eri; Lim, Chang-Kweng; Saijo, Masayuki
Abstract: Dengue is a febrile illness caused by the dengue virus (DENV) that belongs to the genus Flavivirus in the family Flaviviridae . Cross-reactivity between flaviviruses poses a challenge while interpreting serological test results. In the present study, the cross-reactivity of sera of the patients with dengue, who traveled from Japan to DENV-endemic countries, was analyzed by using an enzyme-linked immunosorbent assay (ELISA) and neutralization test (NT). Sixteen serum samples were collected from patients with dengue and were tested for: i) IgM antibodies against Zika virus (ZIKV), West Nile virus (WNV), Japanese encephalitis virus (JEV), and tick-borne encephalitis virus (TBEV) using IgM ELISA, ii) IgG antibody against TBEV using IgG ELISA, and iii) neutralizing antibody against ZIKV, WNV, TBEV, and JEV. Among the 16 samples tested using ELISA, seven samples were IgM-positive for at least one of the other flaviviruses, and nine samples were IgG-positive for TBEV. Neutralizing antibody titers (NATs) against ZIKV, WNV, and TBEV were one-fourth or lower than those against the causative DENV in all samples. The NATs against JEV were one-fourth or lower than those against the causative DENV in six convalescent-phase serum sample among the seven convalescent-phase serum samples. The NAT against DENV of the residual one convalescent-phase serum was similar to that against JEV and that against JEV of its relevant acute-phase serum sample. These results showed that NTs with paired serum samples are important to correctly interpret the serological test results for DENV.